2015
DOI: 10.1093/infdis/jiv088
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic MulticlonalPlasmodium falciparumInfections Carried Through the Dry Season Predict Protection Against Subsequent Clinical Malaria

Abstract: The results suggest that persistent multiclonal infections carried through the dry season contribute to protection against subsequent febrile malaria, possibly by maintaining protective immune responses that depend on ongoing parasite infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
43
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 37 publications
12
43
2
Order By: Relevance
“…Consistent with prior studies [18][19][20][21][22], asymptomatic P. falciparum infection at the end of the dry season was associated with lower risk of febrile malaria during the ensuing malaria season (p<0.0001; Figure 1C), an association that remained significant after adjusting for age, gender and hemoglobin (Hb) type (P<0.0001; Figure 1D). The risk of febrile malaria was not significantly different between PCR + smear + subjects and PCR + smear -subjects (p=0.51; Figure 1C), indicating that the difference in baseline parasitemia between these groups did not affect subsequent malaria risk.…”
Section: Asymptomatic P Falciparum Infection During the Dry Season Isupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with prior studies [18][19][20][21][22], asymptomatic P. falciparum infection at the end of the dry season was associated with lower risk of febrile malaria during the ensuing malaria season (p<0.0001; Figure 1C), an association that remained significant after adjusting for age, gender and hemoglobin (Hb) type (P<0.0001; Figure 1D). The risk of febrile malaria was not significantly different between PCR + smear + subjects and PCR + smear -subjects (p=0.51; Figure 1C), indicating that the difference in baseline parasitemia between these groups did not affect subsequent malaria risk.…”
Section: Asymptomatic P Falciparum Infection During the Dry Season Isupporting
confidence: 88%
“…We sought to confirm prior studies that associated asymptomatic P. falciparum infection with lower risk of clinical malaria [18,19,21,22]. During a two-week period in May 2011 we enrolled 695 asymptomatic subjects just prior to the 6-month malaria season ( Figure 1A).…”
Section: Asymptomatic P Falciparum Infection During the Dry Season Imentioning
confidence: 88%
See 1 more Smart Citation
“…However, such an interpretation contradicts epidemiological evidence from areas of seasonal transmission where asymptomatic infections persisting during the dry season mostly comprise wild-type parasites [3]. Another study found that the proportion of mixed-genotype infections and the number of genotypes per person was higher among asymptomatic than symptomatic infections and that this diversity of infecting strains might enhance protection against clinical malaria [30]. Additional evidence has further suggested that multiplicity of genotypes could also favor the parasite by extending the duration of infections through the selection of genotypes that ensure parasite survival and transmissibility [31].…”
Section: Multiplicity Of Infection and Drug Resistancementioning
confidence: 95%
“…Asymptomatic carriage of parasites has been shown to be associated with reduced risk of symptomatic malaria [26, 27]. Much of the evidence seem to support the idea that the outcome of a malaria infection is associated with carriage of unique/variant parasite alleles.…”
Section: Introductionmentioning
confidence: 99%